Formal disposal e-waste practices: a study on residents in Bukit Sentosa, Rawang, Selangor - Jordan Ang Tien Yoong; Mastura Azhar; Nur Syasya Syazwani Mohd Nasir; Wan Nurul ‘Atiqah Wan Mohd Fauzi (2024)
The rapid advancement of technology and rising consumer spending power have an impact on the increased use of electronic products. The environment is impacted by rising consumption, whether it is as a result of trash produced after products are used or the extraction of raw materials. In 2019, the global generation of e-waste surpassed 50 million tons. Specifically, within the Asia Pacific region, 24.9 million tons of e-waste were generated Lynda (2021). The increase in the worldwide generation of e-waste outpaced the growth of the global population by threefold Lynda (2021). In Malaysia, theproduction of electronic waste amounted to 706,295 metric tons in 2010 and is projectedto rise to 1,119,155 metric tons by 2023 (Nai, 2018). Electronic waste is defined by DOE (2023) as "a malfunctioning, obsolete, or broken electric electronic appliance." It originates primarily in the industrial and domesticsectors. For formal disposal e-waste refer to all collectors are compulsory for transferringof collected household e-wastes to licensed places which registered under government. Authorized collection centre is a centralized place that collects the e-waste primarily collected from household by collectors. It is important for preventing the leakage of e- waste to the unauthorized channel by DOE (2023).